Site-Specific Conjugation for Fully Controlled Glycoconjugate Vaccine Preparation - Pillot, Aline; Defontaine, Alain; Fateh, Amina; Lambert, Annie; Prasanna, Maruthi; Fanuel, Mathieu; Pipelier, Muriel; Csaba, Noemi; Violo, Typhaine; Camberlein, Emilie; Grandjean, Cyrille (Frontiers in Chemistry, 2019)
Glycoconjugate vaccines are formed of a carbohydrate antigen covalently linked to a carrier protein whose role is to achieve a long lasting immune response directed against the carbohydrate antigen. In addition to the nature of the sugar antigen, its length, its ratio per carrier protein and the conjugation chemistry, it has long been assumed that the sites at which the carbohydrate antigen is attached impact both structure and the immune response. These important issues can now be addressed thanks to the development of novel chemoselective ligation reactions as well as that of techniques such as site-selective mutagenesis, glycoengineering or extension of the genetic code. The preparation and characterization of homogeneous bivalent pneumococcal vaccines is reported. A synthetic tetrasaccharide representative of the serotype 14 capsular polysaccharide of Streptococcus pneumoniae has been linked using the thiol/maleimide coupling chemistry to four different Pneumococcal surface adhesin A (PsaA) mutants, each harboring a single cysteine mutation at a defined position. Humoral response of these 1 to 1 carbohydrate antigen/PsaA conjugates have been assessed in mice. As a result we observed that the carbohydrate antigen-PsaA connectivity impacts the anti-carrier response and questions the design of glycoconjugate vaccine whereby the protein plays the dual role of immunogen and carrier.